Plant immunity against viruses - Yule Liu (Frontiers Research Topics, 2017)
Plant viruses impose a serious threat on agriculture, which motivates extensive breeding efforts for viral resistant crops and inspires lasting interests on basic research to understand the mechanisms underlying plant immunity against viruses. Viruses are obligate intracellular parasites. Their genomes are usually small and only encode a few products that are essential to hijack host machinery for their nucleotide and protein biosynthesis, and that are necessary to suppress host immunity. Plants evolved multilayers of defense mechanisms to defeat viral infection. In this research topic, we gathered 13 papers covering recent advances in different aspects of plant immunity against viruses, including reviews on RNA silencing and R gene based immunity and their application, translational initiation factor mediated recessive resistance, genome editing based viral immunity, role of chloroplast in plant-virus interaction, and research articles providing new mechanistic insights on plant-virus interactions. We hope that this Research Topic helps readers to have a better understanding of the progresses that have been made recently in plant immunity against viruses. A deeper understanding of plant antiviral immunity will facilitate the development of innovative approaches for crop protections and improvements.